Why Are Average Hours Worked Lower in Richer Countries? - Alexander Bick; Nicola Fuchs-Schündeln; David Lagakos; Hitoshi Tsujiyama (Institute of Labor Economics (IZA), 2020)
Why are average hours worked per adult lower in rich countries than in poor countries? We consider two natural explanations: income effects in preferences, in which leisure becomes more valuable when income rises, and distortionary tax systems, which are more prevalent in richer countries. To assess the importance of these two forces, we build a simple model of labor supply by heterogeneous individuals and calibrate it to match international data on labor income taxation, government transfers relative to GDP, and hours worked per adult. The model predicts that income effects are the main driving force behind the decline of average hours worked with GDP per capita. We reach a similar conclusion in an extended model that matches cross-country patterns of labor supply along the extensive and intensive margins and of the prevalence of subsistence self-employment.
Keywords: E24; J22; O11; 330; income effects; hours worked; taxation